Framing of propaganda and negative content in Indonesian media - Roosinda, Fitria Widiyani; Suryandaru, Yayan Sakti (Jurnal Studi Komunikasi, 2020)
The robust development of information has enabled communities to continue to use the internet in various aspects of life. An essential element of information source is social media, which has become an inseparable part of our daily activities. It can be used for various things, one of which is propaganda in politics. Such propaganda impacts the dissemination of misleading information that does not necessarily conform with the core function of mass media. Nevertheless, conflicts of interest caused by media authorities continue to confuse the public regarding information released based on facts or made only for hoax distribution. The purpose of this study was to analyse framing in online news related to propaganda problems and harmful content using the Entman framing method. The practice of hoaxes in cyberspace became a sensational topic after the expose of sites that provided paid hoax news and hate speech in Indonesia during the Indonesian presidential election in 2014. The neutrality of mass media is necessary in order to provide accurate references for the public and to filter out misleading hoaxes. The role of the media institution influences the neutrality of the media. Active participation from the community is also essential in media supervising. Furthermore, the community perceive comfortable in delivering their political participation.